Follow-up Findings in Regional Cerebral Blood Flow (r-CBF)-SPECT in a Case of idiopathic Childhood Hemidystonia - Fiedler, A.; Marienhagen, J.; Aderbauer, Judith; Bock, Elke; Segerer, H.; Eilles, Chr. (Nuklearmedizin - NuclearMedicine, 1999)
A 9½-year-old girl suffered from intermitting tremor and jitteriness of her left hand and oral muscles every 4 to 6 weeks with long lasting episodes. Clinically myoclonias and dystonic positioning of the left arm, hand and facial muscles were seen. No evidence of trauma, infection or inborn errors of metabolism was found. Successful therapy with carbamazepine was initiated while L-DOPA failed. An ictal 99m-Tc-HMPAO-SPECT showed severe asymmetry with focal hyperperfusion of the contralateral right thalamus and basal ganglia as well as of the bifrontal cortex, whereas no anatomical lesions were found by MRI. In contrast, an interictally performed 99m-Tc-HMPAO SPECT showed hypoperfusion of the right thalamus and normalisation of the frontal perfusion under medical treatment. These 99m-Tc-HMPAO-SPECT findings may provide new insights into the localisation and pathophysiological pathways of idiopathic childhood dystonia.
Keywords: Hemidystonia; thalamus; SPECT